FACTORS INFLUENCING MURABAHAH MARGIN LEVELS IN THE ISLAMIC BANKING INDUSTRY, 2012–2017 - Ekawati, Khiaroh; Shofawati, Atina (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2019)
This study aims to determine the effect of Financing to Deposit Ratio, profit sharing of third party funds, overhead cost, and BI rate on Murabahah margin rate in Islamic Bank Industries in Indonesia period 2012-2017. This research use multiple linear regression analysis. There are four independent variable in this research namely Financing to Deposit Ratio, Profit Sharing Of Third Party Funds, Overhead Cost, and BI Rate. The sample in this study used a saturated sample, while data were taken from Islamic Bank Statistic issued by OJK, while BI rate taken from www.bi.go.id. The result show that Financing to Deposit Ratio and profit sharing of thirty party funds has positive and significant effect on the Murabahah margin rate. While overhead cost and BI rate has no effect on the Murabahah margin rate. All the independent variables in this research are simultaneously has significant effect on the Murabahah margin rate.Keywords: Financing to Deposit Ratio (FDR), profit sharing of third party funds, overhead cost, BI rate, Murabahah margin rate.